Environment-friendly green paint and preparation method thereof
Patent Information
- Application Number
- CN202610479064.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-04-13
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2046-04-13
AI Technical Summary
由于水性树脂在制备过程中需引入大量极性亲水单元以实现其水分散效果,这使得水性树脂材料的耐盐雾性以及硬度并不理想,涂层表面存在大量极性位点对于污垢的吸附也给涂层的清洁带来了巨大的挑战
本发明利用偶联剂修饰沸石分子筛,再通过与功能化碳纳米管的反应,构建一个多维度的增强网络,将其作为改性剂加入水性聚氨酯基体中,提高水性聚氨酯涂层的性能。沸石分子筛表面被接枝上氨基,变成氨基化沸石分子筛。而羧基化碳纳米管表面带有羧基,碳纳米管通过键和作用接枝到了沸石分子筛表面或周围,使碳纳米管穿插在沸石分子筛颗粒之间,不仅促进了沸石分子筛以及羧基化碳纳米管的分散,而且促进了羧基化碳纳米管之间交互网络的形成。沸石分子筛本身就是一种无机矿物质,莫氏硬度较高,直接参与构成涂层的骨架可以提高抗压入能力。碳纳米管具有极高的抗拉强度,分散在涂层中可以有效抵抗形变。并且,碳纳米管表面的羧基以及沸石表面接枝的氨基,在涂层固化过程中,也可与水性聚氨酯本身的异氰酸酯基团或基体上的羟基发生额外反应,提高了涂层的交联密度。具有交互结构的碳纳米管-沸石分子筛在涂层中层层堆叠,延长了腐蚀因子的路径;而通过偶联剂改性和化学键合,填料与树脂之间的界面结合力很强,减少了因界面空隙导致的微渗透通道。
Abstract
Description
Technical Field
[0001] This invention belongs to the field of coating technology, specifically relating to a green and environmentally friendly coating and its preparation method. Background Technology
[0002] Corrosion refers to the destructive erosion of metals through chemical or electrochemical reactions with their surrounding environment. Metal corrosion is prevalent in various fields, including daily life, transportation, machinery manufacturing, chemical production, and defense technology; wherever metallic materials are used, corrosion problems of varying degrees will occur. When metals are exposed to air, their surfaces directly corrode chemically with substances such as sulfur compounds and oxygen, while electrochemical corrosion occurs when they come into contact with corrosive media such as acidic or alkaline liquids.
[0003] Therefore, research on the corrosion and protection of metallic materials is receiving increasing attention. Currently, corrosion prevention measures for metal surfaces mainly include: modifying the metal structure (e.g., adding chromium and nickel to steel to create stainless steel); electrochemical protection (e.g., using the principle of a galvanic cell for electroplating protection); altering the surrounding environment of the metal material (e.g., changing temperature, humidity, and acidity / alkalinity); and protective layer methods (e.g., coating the metal surface with a protective layer to isolate it from corrosive media). These methods extend the service life of metallic materials and reduce unnecessary economic losses. Different protective measures can be selected to meet different needs. Currently, the most widely used method is coating protection, which can effectively isolate the metal from corrosive media and provide excellent protection.
[0004] Waterborne resins, as a type of water-dispersible polymer system, possess extremely low volatile organic compound (VOC) content, excellent structural modifiability, and performance comparable to solvent-based resins, perfectly aligning with the current development concept of "green chemistry." Therefore, they have gained widespread attention and use in coating applications in construction, automotive, leather, and printing. However, in some practical applications, water and organic matter are common environmental media, requiring coatings to be exposed to moisture or organic matter for extended periods. This not only necessitates basic physical protection of the substrate but also places higher demands on the coating's water resistance, solvent resistance, antifouling properties, and durability. Because waterborne resins require the introduction of numerous polar hydrophilic units during preparation to achieve water dispersion, their salt spray resistance and hardness are not ideal. Furthermore, the presence of numerous polar sites on the coating surface facilitates dirt adsorption, posing a significant challenge to cleaning. Therefore, balancing the emulsion dispersibility and mechanical properties of waterborne resins while simultaneously imparting considerable salt spray resistance is crucial for the diversified development and large-scale application of functional waterborne resin coatings in the future. Summary of the Invention
[0005] The purpose of this invention is to address the above-mentioned problems by providing a green and environmentally friendly coating and its preparation method. The coating of this invention has high hardness, good salt spray resistance, excellent stability, and broad application prospects.
[0006] The technical solution of this invention is implemented as follows: A method for preparing a green and environmentally friendly coating includes the following steps: (1) Disperse the aminosilane coupling agent and zeolite molecular sieve in a solvent and react to obtain the modified zeolite molecular sieve. (2) Carboxylated carbon nanotubes and modified zeolite molecular sieves were ultrasonically dispersed in deionized water, heated to react, vacuum filtered, and dried to obtain carboxylated carbon nanotube modified zeolite molecular sieves; the mass ratio of carboxylated carbon nanotubes to modified zeolite molecular sieves was (1.5-3.5):1. (3) A green and environmentally friendly coating is prepared by mixing water-based polyurethane dispersion, carboxylated carbon nanotube modified zeolite molecular sieve and coating additives evenly.
[0007] As a porous mineral material with a regular pore structure, zeolite molecular sieves have wide applications in waterborne polyurethane systems. They possess cation exchange capacity, allowing them to capture diffused cations and inhibit cathodic reactions in the microenvironment where corrosion occurs. Furthermore, waterborne polyurethane is prone to bubble formation during curing, leading to pinholes or blistering in the coating and severely impacting performance. Zeolite molecular sieves act like a strong sponge, effectively preventing bubble formation, ensuring a dense and smooth coating, and extending the coating's pot life. However, as an inorganic filler, zeolite molecular sieves exhibit poor dispersibility in waterborne polyurethane systems and are prone to sedimentation, resulting in degraded coating performance. Carbon nanotubes, with their ultra-high aspect ratio and tensile strength, can significantly improve the mechanical properties of waterborne polyurethane coatings, such as tensile strength, flexibility, and impact resistance. Even very low addition amounts can significantly affect the viscoelasticity and toughness of polyurethane. However, carbon nanotubes also present compatibility issues. Therefore, combining zeolite molecular sieves and carbon nanotubes to fully utilize their properties to improve the performance of waterborne polyurethane coatings remains a challenge.
[0008] Therefore, this invention utilizes a coupling agent to modify zeolite molecular sieves, and then, through reaction with functionalized carbon nanotubes, constructs a multi-dimensional reinforcing network. This network is then added as a modifier to the waterborne polyurethane matrix to improve the performance of the waterborne polyurethane coating. First, the aminosilane coupling agent, through the hydrolysis of its siloxane groups, undergoes a condensation reaction with the hydroxyl groups on the surface of the zeolite molecular sieve, grafting amino groups onto the zeolite molecular sieve surface, transforming it into an aminated zeolite molecular sieve. Meanwhile, the carboxylated carbon nanotubes have carboxyl groups on their surface. When amino groups encounter carboxyl groups, under heating conditions, the two readily form strong hydrogen bonds or undergo amidation reactions to form amide bonds. As a result, carbon nanotubes are grafted onto or around the surface of the zeolite molecular sieve through bonding interactions, allowing the carbon nanotubes to interpenetrate between the zeolite molecular sieve particles. This not only promotes the dispersion of the zeolite molecular sieve and carboxylated carbon nanotubes but also promotes the formation of an interactive network among the carboxylated carbon nanotubes. Zeolite molecular sieves themselves are inorganic minerals with high Mohs hardness; their direct participation in the formation of the coating's framework can improve its resistance to indentation. Carbon nanotubes possess extremely high tensile strength, effectively resisting deformation when dispersed in coatings. Furthermore, the carboxyl groups on the carbon nanotube surface and the amino groups grafted onto the zeolite surface can react additionally with the isocyanate groups of the waterborne polyurethane itself or the hydroxyl groups on the matrix during coating curing, increasing the crosslinking density of the coating. The interlayered carbon nanotube-zeolite molecular sieve structure in the coating extends the pathway of corrosive agents; and through coupling agent modification and chemical bonding, the interfacial bonding between the filler and the resin is strong, reducing micropermeability channels caused by interfacial voids.
[0009] In one embodiment, the mass ratio of carboxylated carbon nanotubes to modified zeolite molecular sieves is (2-3.2):1. A suitable ratio of carboxylated carbon nanotubes to modified zeolite molecular sieves can fully utilize the adsorption effect of zeolite molecular sieves and allow carboxylated carbon nanotubes to fully modify zeolite molecular sieves, thereby improving their dispersion performance in waterborne polyurethane.
[0010] In one embodiment, the aminosilane coupling agent in step (1) is one or more of (3-aminopropyl)trimethoxysilane, (3-aminopropyl)methyldimethoxysilane, (3-aminopropyl)dimethylmethoxysilane, (3-aminopropyl)triethoxysilane, (3-aminopropyl)methyldiethoxysilane, (3-aminopropyl)dimethylethoxysilane, N-β-aminoethyl-γ-aminopropyltrimethoxysilane, N-β-aminoethyl-γ-aminopropyltriethoxysilane, N-β-aminoethyl-γ-aminopropylmethyldimethoxysilane, and N-β-aminoethyl-γ-aminopropylmethyldiethoxysilane.
[0011] In one embodiment, the mass ratio of aminosilane coupling agent to zeolite molecular sieve in step (1) is (0.3-0.8):1. Specifically, the mass ratio of aminosilane coupling agent to zeolite molecular sieve is 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, or 0.8:1. Further, the mass ratio of aminosilane coupling agent to zeolite molecular sieve is (0.4-0.6):1. An appropriate amount of aminosilane coupling agent can modify the zeolite molecular sieve while avoiding excessive modification that could damage the pore structure of the zeolite molecular sieve, thus fully utilizing its adsorption modification effect on carboxyl carbon nanotubes.
[0012] In one embodiment, the zeolite molecular sieve particle size in step (1) is 1-4 µm. Specifically, the zeolite molecular sieve particle size can be 1.0 µm, 1.5 µm, 2.0 µm, 2.5 µm, 3.0 µm, 3.5 µm, or 4.0 µm. In particular, it can be 1.5-3.5 µm. By selecting a suitable size of zeolite molecular sieve, it can better serve as an interactive carrier for carboxylated carbon nanotubes. If the particle size is too small, it is not conducive to exerting its porous adsorption effect and it is difficult to load a sufficient amount of carboxylated carbon nanotubes; if the particle size is too large, it is easy to cause the zeolite molecular sieve itself to be difficult to disperse.
[0013] In one embodiment, the solvent in step (1) is a mixed solution of ethanol and deionized water. Specifically, a mixed solution of ethanol and deionized water in a volume ratio of 1:1 can be selected.
[0014] In one embodiment, the reaction temperature in step (1) is 50-70°C, and the reaction time is 2-4 h. Specifically, the reaction temperature is 55-65°C, and the reaction time is 2.5-3.5 h. Appropriate reaction temperature and time can ensure uniform modification of zeolite molecular sieves by aminosilane coupling agents, which is beneficial for subsequent bonding with carboxylated carbon nanotubes.
[0015] In one embodiment, the carboxylated carbon nanotubes in step (2) are carbon nanotubes treated with a strong oxidizing acid.
[0016] In one embodiment, the specific preparation process of carboxylated carbon nanotubes in step (2) is as follows: Carbon nanotubes are placed in a mixed solution of concentrated sulfuric acid and concentrated nitric acid (volume ratio of concentrated sulfuric acid (98 wt%) to concentrated nitric acid (68 wt%) is 3:1) and reacted at 55-65°C for 3-5 hours. After washing and drying, carboxylated carbon nanotubes are obtained. Carbon nanotubes have a large aspect ratio; their diameter is generally only 1-60 nm, while their length can reach 100 μm. The type of carbon nanotube used in this invention is not particularly limited; any commonly used type in the art can be used. Specifically, carbon nanotubes with a diameter of 5-50 nm and a length of 5-50 μm commonly used in the art can be used. In particular, in a specific embodiment of this invention, ordinary carbon nanotubes with a diameter of 10-30 nm and a length of 10-30 μm are used.
[0017] In one embodiment, the ultrasonic power in step (2) is 100-200W. Specifically, the ultrasonic power is 120W-180W. If the ultrasonic energy is insufficient, the strong van der Waals forces between the carboxylated carbon nanotubes and the modified zeolite molecular sieve cannot be overcome, and they will exist in the form of aggregates. Not only will they fail to exert the nano-reinforcement effect, but they may also become stress concentration points, leading to a decrease in the mechanical properties of the coating. Furthermore, the cavitation effect generated by high-energy ultrasound will release huge local energy, which can easily damage the structure of the carboxylated carbon nanotubes and the modified zeolite molecular sieve, resulting in a decrease in their mechanical properties.
[0018] In one embodiment, the heating temperature in step (2) is 75-85°C and the reaction time is 3-6 hours.
[0019] In one embodiment, the drying temperature in step (2) is not particularly limited, but can be 70-100°C. Further, the present invention uses a vacuum filtration method to prepare carboxylated carbon nanotube-modified zeolite molecular sieves. Vacuum filtration can be performed using a vacuum filtration device commonly used in the art, and the filtration pressure is not particularly limited; conventional pressures of -0.03 to -0.1 MPa are acceptable. Specifically, pressures between -0.04 to -0.09 MPa or -0.05 to -0.07 MPa can be used. Through vacuum filtration, the moisture on the surface and inside the pores of the zeolite-modified molecular sieve is rapidly removed, generating negative pressure. This not only facilitates the full bonding of the carboxylated carbon nanotubes with the active groups on the surface of the zeolite molecular sieve, but also enables self-assembly, achieving uniform mixing and orderly stacking of the two materials at the microscale. Furthermore, the close contact in the stacked state promotes the reaction between amino and carboxyl groups or the formation of hydrogen bonds during filtration and drying.
[0020] In one embodiment, the solid content of the aqueous polyurethane dispersion in step (3) is 50-70%.
[0021] In one embodiment, the mass ratio of carboxylated carbon nanotube-modified zeolite molecular sieve to aqueous polyurethane dispersion in step (3) is (8-12):100. Further, the mass ratio of carboxylated carbon nanotube-modified zeolite molecular sieve to aqueous polyurethane dispersion is 8:100, 9:100, 10:100, 11:100, or 12:100.
[0022] In one embodiment, the coating additive in step (3) is one or more of the following: anti-settling agent, defoamer, wetting and dispersing agent.
[0023] In one embodiment, the mass ratio of anti-settling agent, defoamer, wetting and dispersing agent to aqueous polyurethane dispersion in step (3) is (1-2):(1-2):(1-2):100.
[0024] In one embodiment, the anti-settling agent in step (3) is one or more of BYK420, BYK425, and BYK430.
[0025] In one embodiment, the defoamer in step (3) is an organosilicone defoamer or a mineral oil defoamer. Specifically, it can be polydimethylsiloxane.
[0026] In one embodiment, the wetting and dispersing agent in step (3) is one or more of sodium polyacrylate, ammonium polyacrylate, and polyphosphate. Specifically, it can be sodium polyacrylate.
[0027] On the other hand, the present invention also provides a green and environmentally friendly coating prepared by the above method. This green and environmentally friendly coating has excellent mechanical properties and anti-corrosion properties, and can be widely used in high humidity and high corrosion environments.
[0028] Beneficial effects: This invention utilizes a coupling agent to modify zeolite molecular sieves, and then, through reaction with functionalized carbon nanotubes, constructs a multi-dimensional reinforcing network. This network is then added as a modifier to an aqueous polyurethane matrix to improve the performance of the aqueous polyurethane coating. The zeolite molecular sieve surface is grafted with amino groups, becoming an aminated zeolite molecular sieve. Meanwhile, the carboxylated carbon nanotubes, with carboxyl groups on their surface, are grafted onto or around the zeolite molecular sieve surface through bonding interactions, allowing the carbon nanotubes to interpenetrate between the zeolite molecular sieve particles. This not only promotes the dispersion of both the zeolite molecular sieve and the carboxylated carbon nanotubes but also fosters the formation of an interactive network among the carboxylated carbon nanotubes. Zeolite molecular sieves themselves are inorganic minerals with high Mohs hardness; their direct participation in forming the coating framework enhances indentation resistance. Carbon nanotubes possess extremely high tensile strength, and their dispersion in the coating effectively resists deformation. Furthermore, the carboxyl groups on the surface of carbon nanotubes and the amino groups grafted onto the surface of zeolite can react additionally with the isocyanate groups of the waterborne polyurethane itself or the hydroxyl groups on the matrix during the coating curing process, thereby increasing the crosslinking density of the coating. The carbon nanotube-zeolite molecular sieve with its interactive structure is stacked layer by layer in the coating, extending the path of corrosive agents; while through coupling agent modification and chemical bonding, the interfacial bonding force between the filler and the resin is very strong, reducing the micropermeability channels caused by interfacial voids. Detailed Implementation
[0029] To better illustrate the purpose, technical solution, and advantages of this application, the following will provide further explanation with reference to specific embodiments. In the following embodiments and comparative examples, the experimental methods used are all conventional methods, and the materials and reagents used are all commercially available.
[0030] Unless otherwise specified, the specific processes and process parameters used in the following embodiments and comparative examples are the same.
[0031] The methods for preparing carboxylated carbon nanotubes used in the following examples and comparative examples are as follows: Carbon nanotubes were placed in a mixed solution of concentrated sulfuric acid and concentrated nitric acid (volume ratio of concentrated sulfuric acid (concentration of 98 wt%) to concentrated nitric acid (concentration of 68 wt%) was 3:1), reacted at 60°C for 4 h, and then washed and dried to obtain carboxylated carbon nanotubes.
[0032] Performance testing: Parallel experiments were conducted to test the hardness (GB / T 6739-2006) and salt spray resistance (GB / T 1771-2007) of the green and environmentally friendly coatings prepared in the following examples and comparative examples. Example 1
[0033] A method for preparing a green and environmentally friendly coating includes the following steps: (1) The aminosilane coupling agent (3-aminopropyl)trimethoxysilane and zeolite molecular sieve were dispersed in a mixed solution of ethanol and deionized water in a volume ratio of 1:1 and reacted at 50°C for 4 h to obtain modified zeolite molecular sieve; the mass ratio of aminosilane coupling agent to zeolite molecular sieve was 0.3:1; the particle size of zeolite molecular sieve was 1.5µm; (2) Carboxylated carbon nanotubes and modified zeolite molecular sieves were ultrasonically dispersed in deionized water at 150W, heated at 75℃ for 6h, vacuum filtered, and dried at 80℃ to obtain carboxylated carbon nanotube modified zeolite molecular sieves; the mass ratio of carboxylated carbon nanotubes to modified zeolite molecular sieves was 1.8:1. (3) A green and environmentally friendly coating is prepared by uniformly mixing an aqueous polyurethane dispersion (60% solid content), a carboxylated carbon nanotube modified zeolite molecular sieve, an anti-settling agent BYK420, an antifoaming agent polydimethylsiloxane, and a wetting and dispersing agent sodium polyacrylate. The mass ratio of the carboxylated carbon nanotube modified zeolite molecular sieve to the aqueous polyurethane dispersion is 8:100; the mass ratio of the anti-settling agent, antifoaming agent, wetting and dispersing agent to the aqueous polyurethane dispersion is 2:2:2:100. The coating was tested and found to have a hardness of 2H and a salt spray resistance of 790h. Example 2
[0034] A method for preparing a green and environmentally friendly coating includes the following steps: (1) The aminosilane coupling agent (3-aminopropyl)triethoxysilane and zeolite molecular sieve were dispersed in a mixed solution of ethanol and deionized water in a volume ratio of 1:1 and reacted at 70°C for 2 h to obtain modified zeolite molecular sieve; the mass ratio of aminosilane coupling agent to zeolite molecular sieve was 0.8:1; the particle size of zeolite molecular sieve was 3.5µm; (2) Carboxylated carbon nanotubes and modified zeolite molecular sieves were ultrasonically dispersed in deionized water at 150W, heated at 85℃ for 3h, vacuum filtered, and dried at 80℃ to obtain carboxylated carbon nanotube modified zeolite molecular sieves; the mass ratio of carboxylated carbon nanotubes to modified zeolite molecular sieves was 3.5:1. (3) A green and environmentally friendly coating is prepared by uniformly mixing an aqueous polyurethane dispersion (60% solid content), a carboxylated carbon nanotube modified zeolite molecular sieve, an anti-settling agent BYK425, an antifoaming agent polydimethylsiloxane, and a wetting and dispersing agent sodium polyacrylate. The mass ratio of the carboxylated carbon nanotube modified zeolite molecular sieve to the aqueous polyurethane dispersion is 12:100; the mass ratio of the anti-settling agent, antifoaming agent, wetting and dispersing agent to the aqueous polyurethane dispersion is 1:1:1:100. The coating was tested and found to have a hardness of 3H and a salt spray resistance of 960h. Example 3
[0035] A method for preparing a green and environmentally friendly coating includes the following steps: (1) The aminosilane coupling agent (3-aminopropyl)trimethoxysilane and zeolite molecular sieve were dispersed in a mixed solution of ethanol and deionized water in a volume ratio of 1:1 and reacted at 60°C for 3 h to obtain modified zeolite molecular sieve; the mass ratio of aminosilane coupling agent to zeolite molecular sieve was 0.5:1; the particle size of zeolite molecular sieve was 1µm. (2) Carboxylated carbon nanotubes and modified zeolite molecular sieves were ultrasonically dispersed in deionized water at 150W, heated at 80℃ for 5h, vacuum filtered, and dried at 80℃ to obtain carboxylated carbon nanotubes modified zeolite molecular sieves; the mass ratio of carboxylated carbon nanotubes to modified zeolite molecular sieves was 2.8:1. (3) A green and environmentally friendly coating is prepared by uniformly mixing an aqueous polyurethane dispersion (60% solid content), a carboxylated carbon nanotube modified zeolite molecular sieve, an anti-settling agent BYK420, an antifoaming agent polydimethylsiloxane, and a wetting and dispersing agent sodium polyacrylate. The mass ratio of the carboxylated carbon nanotube modified zeolite molecular sieve to the aqueous polyurethane dispersion is 10:100; the mass ratio of the anti-settling agent, antifoaming agent, wetting and dispersing agent to the aqueous polyurethane dispersion is 1.5:2:1.5:100. The coating was tested and found to have a hardness of 3H and a salt spray resistance of 880h. Example 4
[0036] A method for preparing a green and environmentally friendly coating includes the following steps: (1) The aminosilane coupling agent (3-aminopropyl)triethoxysilane and zeolite molecular sieve were dispersed in a mixed solution of ethanol and deionized water in a volume ratio of 1:1 and reacted at 50°C for 2 h to obtain modified zeolite molecular sieve; the mass ratio of aminosilane coupling agent to zeolite molecular sieve was 0.7:1; the particle size of zeolite molecular sieve was 1.7µm; (2) Carboxylated carbon nanotubes and modified zeolite molecular sieves were ultrasonically dispersed in deionized water at 150W, heated at 78℃ for 3.5h, vacuum filtered, and dried at 80℃ to obtain carboxylated carbon nanotube modified zeolite molecular sieves; the mass ratio of carboxylated carbon nanotubes to modified zeolite molecular sieves was 2.0:1. (3) A green and environmentally friendly coating is prepared by uniformly mixing an aqueous polyurethane dispersion (60% solid content), carboxylated carbon nanotube modified zeolite molecular sieve, anti-settling agent BYK420, defoamer polydimethylsiloxane, and wetting and dispersing agent sodium polyacrylate; the mass ratio of carboxylated carbon nanotube modified zeolite molecular sieve to aqueous polyurethane dispersion is 9:100; the mass ratio of anti-settling agent, defoamer, wetting and dispersing agent to aqueous polyurethane dispersion is 1.2:2:1.2:100. The coating was tested and found to have a hardness of 2H and a salt spray resistance of 860h. Example 5
[0037] A method for preparing a green and environmentally friendly coating includes the following steps: (1) The aminosilane coupling agent (3-aminopropyl)trimethoxysilane and zeolite molecular sieve were dispersed in a mixed solution of ethanol and deionized water in a volume ratio of 1:1 and reacted at 60°C for 3 h to obtain modified zeolite molecular sieve; the mass ratio of aminosilane coupling agent to zeolite molecular sieve was 0.5:1; the particle size of zeolite molecular sieve was 4µm. (2) Carboxylated carbon nanotubes and modified zeolite molecular sieves were ultrasonically dispersed in deionized water at 150W, heated at 80℃ for 5h, vacuum filtered, and dried at 80℃ to obtain carboxylated carbon nanotubes modified zeolite molecular sieves; the mass ratio of carboxylated carbon nanotubes to modified zeolite molecular sieves was 2.8:1. (3) A green and environmentally friendly coating is prepared by uniformly mixing an aqueous polyurethane dispersion (60% solid content), a carboxylated carbon nanotube modified zeolite molecular sieve, an anti-settling agent BYK420, an antifoaming agent polydimethylsiloxane, and a wetting and dispersing agent sodium polyacrylate. The mass ratio of the carboxylated carbon nanotube modified zeolite molecular sieve to the aqueous polyurethane dispersion is 10:100; the mass ratio of the anti-settling agent, antifoaming agent, wetting and dispersing agent to the aqueous polyurethane dispersion is 1.5:2:1.5:100. The coating was tested and found to have a hardness of 3H and a salt spray resistance of 850h. Example 6
[0038] A method for preparing a green and environmentally friendly coating includes the following steps: (1) The aminosilane coupling agent (3-aminopropyl)triethoxysilane and zeolite molecular sieve were dispersed in a mixed solution of ethanol and deionized water in a volume ratio of 1:1 and reacted at 55℃ for 2.6 h to obtain modified zeolite molecular sieve; the mass ratio of aminosilane coupling agent to zeolite molecular sieve was 0.5:1; the particle size of zeolite molecular sieve was 2µm; (2) Carboxylated carbon nanotubes and modified zeolite molecular sieves were ultrasonically dispersed in deionized water at 150W, heated at 77℃ for 5.5h, vacuum filtered, and dried at 80℃ to obtain carboxylated carbon nanotube modified zeolite molecular sieves; the mass ratio of carboxylated carbon nanotubes to modified zeolite molecular sieves was 2.3:1. (3) A green and environmentally friendly coating is prepared by uniformly mixing an aqueous polyurethane dispersion (60% solid content), a carboxylated carbon nanotube modified zeolite molecular sieve, an anti-settling agent BYK425, an antifoaming agent polydimethylsiloxane, and a wetting and dispersing agent sodium polyacrylate. The mass ratio of the carboxylated carbon nanotube modified zeolite molecular sieve to the aqueous polyurethane dispersion is 9.5:100; the mass ratio of the anti-settling agent, antifoaming agent, wetting and dispersing agent to the aqueous polyurethane dispersion is 1.3:1.4:1.3:100. The coating was tested and found to have a hardness of 3H and a salt spray resistance of 830h. Example 7
[0039] A method for preparing a green and environmentally friendly coating includes the following steps: (1) The aminosilane coupling agent (3-aminopropyl)trimethoxysilane and zeolite molecular sieve were dispersed in a mixed solution of ethanol and deionized water in a volume ratio of 1:1 and reacted at 60°C for 3 h to obtain modified zeolite molecular sieve; the mass ratio of aminosilane coupling agent to zeolite molecular sieve was 0.5:1; the particle size of zeolite molecular sieve was 2.2µm; (2) Carboxylated carbon nanotubes and modified zeolite molecular sieves were ultrasonically dispersed in deionized water at 150W, heated at 80℃ for 5h, vacuum filtered, and dried at 80℃ to obtain carboxylated carbon nanotube modified zeolite molecular sieves; the mass ratio of carboxylated carbon nanotubes to modified zeolite molecular sieves was 1.5:1. (3) A green and environmentally friendly coating is prepared by uniformly mixing an aqueous polyurethane dispersion (60% solid content), a carboxylated carbon nanotube modified zeolite molecular sieve, an anti-settling agent BYK420, an antifoaming agent polydimethylsiloxane, and a wetting and dispersing agent sodium polyacrylate. The mass ratio of the carboxylated carbon nanotube modified zeolite molecular sieve to the aqueous polyurethane dispersion is 10:100; the mass ratio of the anti-settling agent, antifoaming agent, wetting and dispersing agent to the aqueous polyurethane dispersion is 1.5:2:1.5:100. The coating was tested and found to have a hardness of 2H and a salt spray resistance of 840h. Example 8
[0040] A method for preparing a green and environmentally friendly coating includes the following steps: (1) The aminosilane coupling agent (3-aminopropyl)triethoxysilane and zeolite molecular sieve were dispersed in a mixed solution of ethanol and deionized water in a volume ratio of 1:1 and reacted at 65°C for 3.3 h to obtain modified zeolite molecular sieve; the mass ratio of aminosilane coupling agent to zeolite molecular sieve was 0.7:1; the particle size of zeolite molecular sieve was 3.2µm; (2) Carboxylated carbon nanotubes and modified zeolite molecular sieves were ultrasonically dispersed in deionized water at 150W, heated at 82℃ for 5h, vacuum filtered, and dried at 80℃ to obtain carboxylated carbon nanotube modified zeolite molecular sieves; the mass ratio of carboxylated carbon nanotubes to modified zeolite molecular sieves was 3.2:1. (3) A green and environmentally friendly coating is prepared by uniformly mixing an aqueous polyurethane dispersion (60% solid content), a carboxylated carbon nanotube modified zeolite molecular sieve, an anti-settling agent BYK430, an antifoaming agent polydimethylsiloxane, and a wetting and dispersing agent sodium polyacrylate. The mass ratio of the carboxylated carbon nanotube modified zeolite molecular sieve to the aqueous polyurethane dispersion is 11:100; the mass ratio of the anti-settling agent, antifoaming agent, wetting and dispersing agent to the aqueous polyurethane dispersion is 1.6:1.7:1.8:100. The coating was tested and found to have a hardness of 3H and a salt spray resistance of 910h. Example 9
[0041] A method for preparing a green and environmentally friendly coating includes the following steps: (1) The aminosilane coupling agent (3-aminopropyl)trimethoxysilane and zeolite molecular sieve were dispersed in a mixed solution of ethanol and deionized water in a volume ratio of 1:1 and reacted at 60℃ for 3.6 h to obtain modified zeolite molecular sieve; the mass ratio of aminosilane coupling agent to zeolite molecular sieve was 0.5:1; the particle size of zeolite molecular sieve was 2.8µm; (2) Carboxylated carbon nanotubes and modified zeolite molecular sieves were ultrasonically dispersed in deionized water at 150W, heated at 80℃ for 4h, vacuum filtered, and dried at 80℃ to obtain carboxylated carbon nanotubes modified zeolite molecular sieves; the mass ratio of carboxylated carbon nanotubes to modified zeolite molecular sieves was 2.5:1. (3) A green and environmentally friendly coating is prepared by uniformly mixing an aqueous polyurethane dispersion (60% solid content), a carboxylated carbon nanotube modified zeolite molecular sieve, an anti-settling agent BYK420, an antifoaming agent polydimethylsiloxane, and a wetting and dispersing agent sodium polyacrylate. The mass ratio of the carboxylated carbon nanotube modified zeolite molecular sieve to the aqueous polyurethane dispersion is 10.5:100; the mass ratio of the anti-settling agent, antifoaming agent, wetting and dispersing agent to the aqueous polyurethane dispersion is 1.1:1.9:1.7:100. The coating was tested and found to have a hardness of 3H and a salt spray resistance of 870h. Example 10
[0042] A method for preparing a green and environmentally friendly coating includes the following steps: (1) The aminosilane coupling agent (3-aminopropyl)trimethoxysilane and zeolite molecular sieve were dispersed in a mixed solution of ethanol and deionized water in a volume ratio of 1:1 and reacted at 60°C for 3 h to obtain modified zeolite molecular sieve; the mass ratio of aminosilane coupling agent to zeolite molecular sieve was 0.5:1; the particle size of zeolite molecular sieve was 2.2µm; (2) Carboxylated carbon nanotubes and modified zeolite molecular sieves were ultrasonically dispersed in deionized water at 150W, heated at 80℃ for 5h, vacuum filtered, and dried at 80℃ to obtain carboxylated carbon nanotubes modified zeolite molecular sieves; the mass ratio of carboxylated carbon nanotubes to modified zeolite molecular sieves was 2.8:1. (3) A green and environmentally friendly coating is prepared by uniformly mixing an aqueous polyurethane dispersion (60% solid content), a carboxylated carbon nanotube modified zeolite molecular sieve, an anti-settling agent BYK420, an antifoaming agent polydimethylsiloxane, and a wetting and dispersing agent sodium polyacrylate. The mass ratio of the carboxylated carbon nanotube modified zeolite molecular sieve to the aqueous polyurethane dispersion is 10:100; the mass ratio of the anti-settling agent, antifoaming agent, wetting and dispersing agent to the aqueous polyurethane dispersion is 1.5:2:1.5:100. The coating was tested and found to have a hardness of 3H and a salt spray resistance of 920h.
[0043] Comparative Example 1 A method for preparing a green and environmentally friendly coating includes the following steps: (1) The aminosilane coupling agent (3-aminopropyl)trimethoxysilane and zeolite molecular sieve were dispersed in a mixed solution of ethanol and deionized water in a volume ratio of 1:1 and reacted at 60°C for 3 h to obtain modified zeolite molecular sieve; the mass ratio of aminosilane coupling agent to zeolite molecular sieve was 0.5:1; the particle size of zeolite molecular sieve was 2.2µm; (2) Carboxylated carbon nanotubes and modified zeolite molecular sieves were ultrasonically dispersed in deionized water at 150W, heated at 80℃ for 5h, filtered at normal pressure, and dried at 80℃ to obtain carboxylated carbon nanotube modified zeolite molecular sieves; the mass ratio of carboxylated carbon nanotubes to modified zeolite molecular sieves was 2.8:1. (3) A green and environmentally friendly coating is prepared by uniformly mixing an aqueous polyurethane dispersion (60% solid content), a carboxylated carbon nanotube modified zeolite molecular sieve, an anti-settling agent BYK420, an antifoaming agent polydimethylsiloxane, and a wetting and dispersing agent sodium polyacrylate. The mass ratio of the carboxylated carbon nanotube modified zeolite molecular sieve to the aqueous polyurethane dispersion is 10:100; the mass ratio of the anti-settling agent, the antifoaming agent, the wetting and dispersing agent to the aqueous polyurethane dispersion is 1.5:2:1.5:100. The coating was tested and found to have a hardness of H and a salt spray resistance of 670h.
[0044] Comparative Example 2 A method for preparing a green and environmentally friendly coating includes the following steps: (1) The aminosilane coupling agent (3-aminopropyl)trimethoxysilane and zeolite molecular sieve were dispersed in a mixed solution of ethanol and deionized water in a volume ratio of 1:1 and reacted at 60°C for 3 h to obtain modified zeolite molecular sieve; the mass ratio of aminosilane coupling agent to zeolite molecular sieve was 0.5:1; the particle size of zeolite molecular sieve was 2.2µm; (2) Carboxylated carbon nanotubes and modified zeolite molecular sieves were ultrasonically dispersed in deionized water at 150W, heated at 80℃ for 5h, vacuum filtered, and dried at 80℃ to obtain carboxylated carbon nanotube modified zeolite molecular sieves; the mass ratio of carboxylated carbon nanotubes to modified zeolite molecular sieves was 5:1. (3) A green and environmentally friendly coating is prepared by uniformly mixing an aqueous polyurethane dispersion (60% solid content), a carboxylated carbon nanotube modified zeolite molecular sieve, an anti-settling agent BYK420, an antifoaming agent polydimethylsiloxane, and a wetting and dispersing agent sodium polyacrylate. The mass ratio of the carboxylated carbon nanotube modified zeolite molecular sieve to the aqueous polyurethane dispersion is 10:100; the mass ratio of the anti-settling agent, antifoaming agent, wetting and dispersing agent to the aqueous polyurethane dispersion is 1.5:2:1.5:100. The coating was tested and found to have a hardness of 3H and a salt spray resistance of 750h.
[0045] As can be seen from the above embodiments and comparative examples, this invention utilizes a coupling agent to modify zeolite molecular sieves, and then, through reaction with functionalized carbon nanotubes, constructs a multi-dimensional reinforcing network. This network is then added as a modifier to the waterborne polyurethane matrix to improve the performance of the waterborne polyurethane coating. The zeolite molecular sieve surface is grafted with amino groups, becoming an aminated zeolite molecular sieve. The carboxylated carbon nanotubes, with carboxyl groups on their surface, are grafted onto or around the zeolite molecular sieve surface through bonding, allowing the carbon nanotubes to interpenetrate between the zeolite molecular sieve particles. This not only promotes the dispersion of both the zeolite molecular sieve and the carboxylated carbon nanotubes but also promotes the formation of an interactive network among the carboxylated carbon nanotubes. Zeolite molecular sieves themselves are inorganic minerals with high Mohs hardness; their direct participation in forming the coating framework can improve indentation resistance. Carbon nanotubes possess extremely high tensile strength, and their dispersion in the coating can effectively resist deformation. Furthermore, the carboxyl groups on the surface of carbon nanotubes and the amino groups grafted onto the surface of zeolite can react additionally with the isocyanate groups of the waterborne polyurethane itself or the hydroxyl groups on the matrix during the coating curing process, thereby increasing the crosslinking density of the coating. The carbon nanotube-zeolite molecular sieve with its interactive structure is stacked layer by layer in the coating, extending the path of corrosive agents; while through coupling agent modification and chemical bonding, the interfacial bonding force between the filler and the resin is very strong, reducing the micropermeability channels caused by interfacial voids.
[0046] Specifically, compared to Example 10, Comparative Example 1 used atmospheric pressure filtration instead of vacuum filtration to remove the solvent, resulting in a significantly worse salt spray resistance in the prepared coating. This is because vacuum filtration rapidly removes moisture from the surface and interior of the zeolite-modified molecular sieve, which not only facilitates the full bonding of carboxylated carbon nanotubes with the active groups on the surface of the zeolite molecular sieve, but also enables self-assembly. This allows for uniform mixing and orderly stacking of the two materials at the microscale, and the close contact in the stacked state promotes reactions or hydrogen bonding between amino and carboxyl groups, which is beneficial for building an interactive network in the waterborne polyurethane coating and improving corrosion resistance. Compared to Example 10, Comparative Example 2 used too many carboxylated carbon nanotubes, resulting in little change in hardness, but a certain degree of decrease in salt spray resistance. This is because there are too many carboxylated carbon nanotubes, exceeding the adsorption and loading capacity of the zeolite molecular sieve. A large number of carboxylated carbon nanotubes are free in the water-based polyurethane coating and agglomeration occurs, which is not conducive to the dispersion of the carboxylated carbon nanotube-modified zeolite molecular sieve that has already been reacted, resulting in reduced coating density and decreased corrosion resistance.
[0047] The technical features of the above embodiments can be combined arbitrarily. For the sake of brevity, not all possible combinations of the technical features in the above embodiments have been described; these embodiments not explicitly stated should also be considered within the scope of this specification. Although the present invention has been described in detail above with general descriptions and specific embodiments, some modifications or improvements can be made to it, which will be obvious to those skilled in the art. Therefore, all such modifications or improvements made without departing from the spirit of the present invention fall within the scope of protection claimed by the present invention.
Claims
1. A method for preparing a green and environmentally friendly coating, characterized in that, Includes the following steps: (1) Disperse the aminosilane coupling agent and zeolite molecular sieve in a solvent and react to obtain the modified zeolite molecular sieve. The mass ratio of aminosilane coupling agent to zeolite molecular sieve is (0.3-0.8):1; (2) Carboxylated carbon nanotubes and modified zeolite molecular sieves were ultrasonically dispersed in deionized water, heated to react, vacuum filtered, and dried to obtain carboxylated carbon nanotube modified zeolite molecular sieves; the mass ratio of carboxylated carbon nanotubes to modified zeolite molecular sieves was (2-3.5):1; the carboxylated carbon nanotubes were carbon nanotubes treated with strong oxidizing acid. (3) A green and environmentally friendly coating is prepared by mixing water-based polyurethane dispersion, carboxylated carbon nanotube modified zeolite molecular sieve and coating additives evenly.
2. The method for preparing a green and environmentally friendly coating as described in claim 1, characterized in that, The reaction temperature in step (1) is 50-70℃ and the reaction time is 2-4h.
3. The method for preparing a green and environmentally friendly coating as described in claim 1, characterized in that, The specific preparation process of carboxylated carbon nanotubes in step (2) is as follows: carbon nanotubes are placed in a mixed solution of concentrated sulfuric acid and concentrated nitric acid, reacted at 55-65℃ for 3-5 hours, and then washed and dried to obtain carboxylated carbon nanotubes.
4. The method for preparing a green and environmentally friendly coating as described in claim 1, characterized in that, The ultrasonic power in step (2) is 100-200W.
5. The method for preparing a green and environmentally friendly coating as described in claim 1, characterized in that, The heating temperature in step (2) is 75-85℃, and the reaction time is 3-6h.
6. The method for preparing a green and environmentally friendly coating as described in claim 1, characterized in that, In step (3), the mass ratio of carboxylated carbon nanotube modified zeolite molecular sieve to aqueous polyurethane dispersion is (8-12):
100.
7. The method for preparing a green and environmentally friendly coating as described in claim 1, characterized in that, In step (3), the coating additive is one or more of the following: anti-settling agent, defoamer, wetting and dispersing agent.
8. A green and environmentally friendly coating, characterized in that, The coating is prepared by any one of the green and environmentally friendly coatings according to any one of claims 1-7.
Citation Information
Patent Citations
Water-based electricity-conducting heat-conducting anticorrosive paint and preparation method thereof
CN118109110A
Graphene zinc water-based heavy anti-corrosion coating with high solid content and application of graphene zinc water-based heavy anti-corrosion coating
CN121801410A
